Kompetensi Moral Guru dalam Menjaga Batas Interaksi dengan Peserta Didik di Era Digital - Nabila Salsa Hidayah; Syahrul Ardiansyah; Muamalatul Hikmah; Muhlisin Muhlisin; Abul Mafaakhir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze teachers’ moral competence in maintaining interaction boundaries with students in the digital era. The development of digital technology had transformed educational interaction patterns from those previously limited to classroom settings into broader communication through social media, instant messaging applications, and online learning platforms. This condition created more flexible communication opportunities, but also presented challenges in maintaining teachers’ professional boundaries. This study used a qualitative approach with a library research method by collecting and analyzing relevant scientific literature. The data were analyzed using content analysis techniques to identify the concept of teachers’ moral competence, changes in educational interaction patterns, and the challenges of professionalism in the digital era. The results showed that teachers’ moral competence played an important role as the foundation of educational professionalism related to integrity, responsibility, and exemplary conduct. In addition, the development of digital interaction had expanded educational communication spaces, requiring teachers to have stronger moral awareness in maintaining interaction boundaries with students. This study confirmed that strengthening teachers’ moral competence was an important necessity in maintaining the quality of educational relationships in the digital era. Keywords: Teacher professionalism, digital interaction, educational ethics ABSTRAK Penelitian ini bertujuan untuk menganalisis kompetensi moral guru dalam menjaga batas interaksi dengan peserta didik di era digital. Perkembangan teknologi digital telah mengubah pola interaksi pendidikan dari yang sebelumnya terbatas pada ruang kelas menjadi lebih luas melalui media sosial, aplikasi pesan instan, dan platform pembelajaran daring. Kondisi ini membuka peluang komunikasi yang lebih fleksibel, tetapi juga menghadirkan tantangan dalam menjaga batas profesional guru. Penelitian ini menggunakan pendekatan kualitatif dengan metode library research melalui pengumpulan dan analisis berbagai literatur ilmiah yang relevan. Data dianalisis menggunakan teknik analisis isi untuk mengidentifikasi konsep kompetensi moral guru, perubahan pola interaksi pendidikan, serta tantangan profesionalisme di era digital. Hasil penelitian menunjukkan bahwa kompetensi moral guru memiliki peran penting sebagai fondasi profesionalisme pendidikan yang berkaitan dengan integritas, tanggung jawab, dan keteladanan. Selain itu, perkembangan interaksi digital telah memperluas ruang komunikasi pendidikan sehingga menuntut guru memiliki kesadaran moral yang lebih kuat dalam menjaga batas interaksi dengan peserta didik. Penelitian ini menegaskan bahwa penguatan kompetensi moral guru menjadi kebutuhan penting dalam menjaga kualitas hubungan pendidikan di era digital. Kata Kunci: Profesionalisme Guru, Interaksi Digital, Etika Pendidikan